KAJIAN ETNOBOTANI PEMANFAATAN TANAMAN PADA UPACARA ADAT OLEH MASYARAKAT DI KAMPUNG ADAT PULO, DESA CANGKUANG, KABUPATEN GARUT - Siti Fatiah, Tifani; Cahyanto, Tri (Universitas Nusa Bangsa, 2024)
Traditional ceremonies are one of the traditions that are still carried out by the people of Kampung Adat Pulo which is located in Cangkuang Village, Leles District, Garut Regency, West Java Province. Traditional ceremonies carried out by the people of Kampung Adat Pulo include; 7 Bulanan, bidang pertanian; Mitembeyan, Hajat panen, Niiskeun pare; and Ngamandikeun Benda Pusaka. The Pulo Traditional Village community uses several plants during these traditional ceremonies. This research aims to find out and collect data on the types of plants used in carried out traditional ceremonies and to find out how to use the plants used in carried out traditional ceremonies in the Pulo Traditional Village. This research uses qualitative methods with field surveys and interviews through purposive sampling as well as quantitative methods to calculate data obtained in the field used the RFC (Relative Frequency of Citation) and ICF (Informant Consensus Factor) formulas. The informants obtained were 11 people with the results showed 14 species with the highest RFC value of 0.9 and the highest ICF value of 0.60.